2011
DOI: 10.1016/j.canlet.2010.09.007
|View full text |Cite
|
Sign up to set email alerts
|

ZEB1-responsive genes in non-small cell lung cancer

Abstract: The epithelial to mesenchymal transition (EMT) is a developmental process enabling epithelial cells to gain a migratory mesenchymal phenotype. In cancer, this process contributes to metastases; however the regulatory signals and mechanistic details are not fully elucidated. Here, we sought to identify the subset of genes regulated in lung cancer by ZEB1, an E-box transcriptional repressor known to induce EMT. Using an Affymetrix-based expression database of 38 non-small cell lung cancer (NSCLC) cell lines, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
140
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(157 citation statements)
references
References 46 publications
14
140
0
2
Order By: Relevance
“…including NSCLC (23,33). Growing evidence suggests that ZEB2 could induce EMT through suppressing E-cadherin expression or inducing vimentin expression, thus facilitating the metastasis of cancer cells (24,25,34,35).…”
Section: D B Amentioning
confidence: 99%
“…including NSCLC (23,33). Growing evidence suggests that ZEB2 could induce EMT through suppressing E-cadherin expression or inducing vimentin expression, thus facilitating the metastasis of cancer cells (24,25,34,35).…”
Section: D B Amentioning
confidence: 99%
“…We also examined the tumour stroma where ZEB1 has been shown previously to be expressed in some tumours 12,23 . Interestingly, we found that the same ZEB1-high, PTEN-low proliferating pattern seen in the K-Ras pathway mutant tumour cells was recapitulated in the tumour-associated stromal fibroblasts (Supplementary Figs 2-5).…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether miR-335 directly targets ZEB2, a dual-luciferase reporter assay was performed; it was revealed that miR-335 significantly decreased the luciferase activity ZEB2, a member of the zinc finger family, functions as a transcriptional repressor of E-cadherin (37). ZEB2 has been identified as upregulated in various types of human cancer, including breast, gastric, head and neck, hepatocellular, ovarian and non-small cell lung carcinoma, and glioma (38)(39)(40)(41)(42)(43)(44). ZEB2 was previously identified as upregulated in PTC cell lines compared with normal thyroid cancer cells (45).…”
Section: Discussionmentioning
confidence: 99%